Pentecostalism and Social Transformation in Southern Africa: A Missiological Approach - Tsara, Lindah (Missionalia, 2024)
Ecological mission is gradually becoming an integral part of the mainstream mission of Pentecostal churches in Ghana. One area that has caught the attention of Pentecostal eco-missionaries in Ghana is the illegal artisanal mining sector, known in the local parlance as galamsey. Illegal artisanal mining activities have led to the destruction of hectares of forests, rendered arable lands unproductive, and pushed many farmers out of employment. While government agencies and civil organisations try to fight it, the church also seeks appropriate biblical responses and missional strategies. This article presents findings from empirical research conducted among leaders and members of Pentecostal churches as well as individuals engaged in illegal mining activities in Tarkwa-Nsuaem Municipality in Ghana. The article highlights the complex relationship between the church and illegal artisanal mining activities. It posits that the church faces a dilemma in its ecological mission due to the benefits it receives from the illegal artisanal mining sector. The situation raises important questions about the church’s role in promoting environmental stewardship and ethical practices in these communities.